Autozygosity mapping in consanguineous Pakistani families identifies nine non-overlapping novel linkage intervals for autosomal recessive non-syndromic mental retardation (AR-NSMR); shows genetic heterogeneity for AR-NSMR - Shoaib-Ur-Rehman; Raaza Malja Khan; Rahmat Ali Khan; Ishtiaq Hussain; Noor Muhammad; Muhammad Arif (Journal of the Pakistan Medical Association, 2021)
Psychological disturbance (PD) or cerebral dysfunction (CD) occupying several clinical areas having defining features of mental retardation. Currently we have designed to investigate heritable heterogeneity in Pakistani consanguineous couples with recessive autosomal intellectual abnormilaties. Department of Biotechnology UST-Bannu and WJC Panum institute University of Copenhagen Denmark from January 2017 to March 2019. Cohort of Three consanguineous families with multiple birth defects was selected from different regions of Pakistan for molecular analysis analysis. All affected individuals in the cohort showed mental disturbances. Deoxyribonucleic acid (DNA) was extracted and subjected to STS (Single tagged sequence) marker analyses to all known non syndromic autosomal recessive mental retardation (NS-ARMR) genes while autozygosity mapping was performed by advanced SNP techniques. STS (Single tagged sequence) marker analyses showed exclusion to all known non syndromic autosomal recessive mental retardation (NS-ARMR) genes. Autozygosity mapping have shown novel nine linkage intervals. Continuous...